This preview shows pages 1–6. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: Vibration absorbers K M F m k t i p t i e M K F x Fe Kx x M 2 ϖ ϖ ϖ = → = + t i e F x x k k k k K x x m M 2 1 2 1 ϖ =  + + Or... 1 2 2 2 1 2 kx kx x m kx kx x m = + = + : Rearrange . : equation Lower ! , and If ∞ → = ≠ = m k kx x x m k 2 1 2 1 2 ϖ ϖ . ) det( 2 2 2 2 ≠ = + = k m k k k M k K ϖ ϖ ϖ But . or resonance, at is system the that indicates this But M K finite. is so frequency, resonant a not is that learned we Also, ". ! , and If " said, We 2 2 1 2 1 2 x m k kx x x m k ϖ ϖ ϖ ∞ → = ≠ = zero! be to is that therefore, conclude, We required 1 x response.) zero a produce we , resonance" " a g introducin (By . 2 1 2 1 2 1 t i t i Fe kx x e F x x k k k k K x x m M ϖ ϖ = = =  + + get we , since : EOM 1st From O bj1 6 5 ? and with system the of s frequencie natural the are What m k s. frequencie natural the are roots two whose in polynomial quadratic a is ) : Consider 2 2 det( ϖ ϖ = M K . ) ( ) det( . ) det( . ) det( 2 2 2 2 2 2 2 2 2 2 → < = = = = = ϖ ϖ ϖ ϖ ϖ ϖ ϖ ϖ Mm k m k Kk M K M K M K , large For , When , When . above frequency another at and and zero between frequency one at zero equals Therefore 2 ) det( ϖ ϖ ϖ M K . above one and quickly) through passed be must (which below resonance one is There ϖ ϖ Nonperiodic response (undamped) . ) ( ) ( ) ( v x x x F x x = = = + , ICs with , : EOMs t K M N η η F η η η x η x = ′ + ′ ⇒ = + = = K M U KU U MU U U t U t t U t T T T T by multiply and , let : approach Modal : ) ( ) ( ) ( ) ( 2 , 1 ) ( = = ′ + ′ i t N k m i i i i i , : EOMs Modal η η systems. SDOF undamped for EOMs to form in identical are EOMs modal These ). ( ) ( . 2 , 1 ) ( 2 , 1 ) ( t U t i t i t N k m i i i i i i η x = = = = ′ + ′ using back transform Then , for , : EOMs modal Solve η η η t t d t m N t i i i i i i t i i i i ϖ ϖ η ϖ η τ τ ϖ ϖ τ η sin ) ( cos ) ( ) ( sin 1 ) ( ) ( + + ′ = ∫ : case general in response Modal ) ( ) ( ) ( ) ( ), ( ) ( ) ( ) ( 1 1 x η η x x η η x  = → = = → = U U U U : from available are ICs Modal etc....
View
Full
Document
This note was uploaded on 09/18/2011 for the course ASE 365 taught by Professor Staff during the Spring '10 term at University of Texas at Austin.
 Spring '10
 Staff

Click to edit the document details